Old Testament Theology. Volume 1. Israel's Gospel. By John Goldingay. Pp. 940. Downers Grove, IL: Inter Varsity Press, 2003. isbn 0 8308 2561 4 - Clements, Ronald Ernest (The journal of theological studies, 2005)
On any reckoning this is a weighty volume and, as the first of three, it will, no doubt, be widely read and reflected on for several years to come. As a subject Old Testament theology has undergone a significant revival of interest, with substantial volumes from H. D. Preuss, W. Brueggemann, R. Knierim, E. Gerstenberger, and Rolf Rendtorff all appearing in recent years. At the same time the centenary celebration for the work of Gerhard von Rad has reopened the debate whether the idea of a salvation-history approach to the subject, which is adopted by Goldingay, provides a new solution to old problems, or simply adds a new one.